Evolution of secondary phases in 0.17C-16Cr-11Mn-0.43N austenitic stainless steel at 800 and 850°C: Thermodynamic modeling of phase equilibria and experimental kinetic studies - Čička R.; Bakajová J.; Štefániková M.; Dománková M.; Janovec J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The precipitation of secondary phases was investigated in the 0.17C-16Cr-11Mn-0.43N austenitic stainless steel during annealing at 800 and 850°C for times between 5 min and 100 h. Light microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy, scanning electron microscopy, and differential thermal analysis were used in experiments. Thermodynamic calculations were done by the ThermoCalc database software package. Cr2N and M23C6 were considered to be stable phases at the annealing temperatures. Cells consisting of alternating Cr2N and austenite lamellae were observed in the steel microstructure after sufficiently long annealing. The metastable chi phase was also found in all the annealed samples. After 100 h of annealing the equilibrium sigma started to precipitate. The thermodynamically predicted M6C was not confirmed experimentally in any of the annealed samples. DTA analysis showed the initial precipitation stage was followed by the phase dissolution. For the investigated steel the computational thermodynamics can be used only for qualitative interpretation of the experimental results as the measured endothermal peaks were found to be shifted of about 50 ÷ 70°C related to the computed results.